Gene gun DNA immunization of cattle induces humoral and CD4 T-cell-mediated immune responses against the Theileria parva polymorphic immunodominant molecule. Issue 12 (14th March 2019) - Fry, Lindsay M.; Bastos, Reginaldo G.; Stone, Brad C.; Williams, Laura B.; Knowles, Donald P.; Murphy, Sean C.
Abstract: Theileria parva kills over one million cattle annually in sub-Saharan Africa. Parasite genetic complexity, cellular response immunodominance, and bovine MHC diversity have precluded traditional vaccine development. One potential solution is gene gun (GG) immunization, which enables simultaneous administration of one or more DNA-encoded antigens. Although promising in murine, porcine, and human vaccination trials, bovine GG immunization studies are limited. We utilized the model T. parva antigen, polymorphic immunodominant molecule (PIM) to test bovine GG immunization. GG immunization using a mammalian codon optimized PIM sequence elicited significant anti-PIM antibody and cell-mediated responses in 7/8 steers, but there was no difference between immunized and control animals following T. parva challenge. The results suggest immunization with PIM, as delivered here, is insufficient to protect cattle from T. parva . Nonetheless, the robust immune responses elicited against this model antigen suggest GG immunization is a promising vaccine platform for T. parva and other bovine pathogens.